Recursive Mathematical Approaches to the Millennium Problems: Toward a Unified Proof - Gujar, Vivek (Journal of Educational Research and Policies, 2025)
This paper presents a formal, unified recursive proof framework that interconnects the seven Millennium Prize Problems into a single mathematical necessity. We establish that if recursion holds as a fundamental property of mathematics, then the resolution of all seven problems follows as an unavoidable consequence. Conversely, if any one problem is found to be unsolvable within this recursive framework, then the entire structure of mathematics collapses, invalidating core principles in computation, physics, and number theory.